2002
DOI: 10.1021/es0112588
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nature of Colloidal Actinides Transported in Surface Water Environments

Abstract: Elevated levels of (239,240)Pu and 241Am have been present in surficial soils of the Rocky Flats Environmental Technology Site (RFETS), CO, since the 1960s, when soils were locally contaminated in the 1960s by leaking drums stored on the 903 Pad. Further dispersion of contaminated soil particles was by wind and water. From 1998 until 2001, we examined actinide ((239,240)Pu and 241Am) concentrations and phase speciation in the surface environment at RFETS through field studies and laboratory experiments. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 23 publications
2
137
0
Order By: Relevance
“…The total reversibility could only be obtained lowering pH to 4 within 24 h, where UO 2+ 2 is the major specie. Under our conditions, we can estimate, referring to Neck and Kim (30), that Th(OH) + 3 and Th(OH) 4 (aq) are the major thorium (IV) species in solution in the interval 6 ≤ pH ≤ 9. As in the case of U(VI), the presence of strongly hydrolysed Th(IV) species can be responsible of the irreversible process.…”
Section: Pre-equilibration Of Hematite and Th(iv)mentioning
confidence: 88%
“…The total reversibility could only be obtained lowering pH to 4 within 24 h, where UO 2+ 2 is the major specie. Under our conditions, we can estimate, referring to Neck and Kim (30), that Th(OH) + 3 and Th(OH) 4 (aq) are the major thorium (IV) species in solution in the interval 6 ≤ pH ≤ 9. As in the case of U(VI), the presence of strongly hydrolysed Th(IV) species can be responsible of the irreversible process.…”
Section: Pre-equilibration Of Hematite and Th(iv)mentioning
confidence: 88%
“…A growing number of field studies, however, document the movement of low concentrations of low-solubility radionuclides in surface and ground waters. 6,9,10 Those small concentrations can be transported in surface water and soils by particles of sizes typically ranging from a nanometer to several microns. 11,12 Because the particles remain suspended in ground water, they can move in the natural watershed and settle into the series of ponds around RFETS.…”
Section: Box 2 X-ray Absorption Spectroscopymentioning
confidence: 99%
“…The bar graph shows a summary of ultrafiltration results from Peter Santschi and colleagues 10 that compares normal discharge (blue) at a particular monitoring station with data recorded shortly after a rainstorm (red). The group's measurements demonstrated that a large majority of the plutonium material that passed the 0.5-μm filter was not dissolved, but colloidal, because it could be filtered out using smaller 0.1-μm filters.…”
Section: Modeling Actinide Transportmentioning
confidence: 99%
“…Furthermore, thorium (IV) and plutonium are known to have the same behaviour in presence of natural organic matter [92]. Nevertheless, readers should bear in mind that these constants are only estimates and should be used with caution.…”
Section: Application To Redox Sensitive Actinide Elementsmentioning
confidence: 99%